Manajemen Sumber Daya Manusia Agribisnis - Lokot Muda Harahap; Syafika; Syarifah Khalisa Adila; Frans Andreas Purba (Lembaga Pengembangan Kinerja Dosen, 2024)
Human Resource Management (HRM) in agribusiness has an important role in increasing the efficiency and productivity of agribusiness businesses. Agribusiness as an important sector in the Indonesian economy requires qualified and competent human resources to improve the quality of the products and services produced. Therefore, agribusiness human resource management must be able to improve the quality and quantity of agricultural production, as well as increase the ability of farmers and breeders to face market changes and environmental changes. In this paper, we will discuss the development of agribusiness human resource management in Indonesia, including strategies that can be used to improve the performance and success of agribusiness businesses.